2014
DOI: 10.1038/nbt.3043
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting CRISPR-Cas nucleases to produce sequence-specific antimicrobials

Abstract: Antibiotics target conserved bacterial cellular pathways or growth functions and therefore cannot selectively kill specific members of a complex microbial population. Here, we develop programmable, sequence-specific antimicrobials using the RNA-guided nuclease Cas91, 2 delivered by a bacteriophage. We show that Cas9 re-programmed to target virulence genes kills virulent, but not avirulent, Staphylococcus aureus. Re-programming the nuclease to target antibiotic resistance genes destroys staphylococcal plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
701
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 808 publications
(723 citation statements)
references
References 30 publications
(42 reference statements)
9
701
2
11
Order By: Relevance
“…Since a large variety of phages exist for any given bacterium, the current trend is the use of 'cocktail' preparations to ensure the presence of multiple phage that target the pathogen in a variety of mechanisms, thus reducing the relatively high frequency of phage resistance exhibited by bacteria. 7,8 Phage therapies are also self-dosing, increasing in numbers at the site of infection only in the presence of their host bacteria. Most phages do not directly display any risk to human health or the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Since a large variety of phages exist for any given bacterium, the current trend is the use of 'cocktail' preparations to ensure the presence of multiple phage that target the pathogen in a variety of mechanisms, thus reducing the relatively high frequency of phage resistance exhibited by bacteria. 7,8 Phage therapies are also self-dosing, increasing in numbers at the site of infection only in the presence of their host bacteria. Most phages do not directly display any risk to human health or the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the CRISPR-Cas system in eliminating plasmid DNA and lytic phages is well established (1,2,15,19,26). Nevertheless, its utility in clinical settings as a tool to render pathogens sensitive to antibiotics and to reduce horizontal gene transfer of resistance determinants has only recently been demonstrated (16,17). We believe that the strategy provided here can be applied to different pathogen-phage systems as phages can be found for most of the pathogens, and a compatible CRISPR-Cas system should work in many pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent elegant studies demonstrated that phage-transferable CRISPR-Cas systems are capable of specifically killing pathogens or resensitizing them to antibiotics (16,17). These studies, and another study (13), also showed that the transferred CRISPR-Cas system is capable of eliminating specific bacterial populations.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Two independent teams believe they could have a farreaching solution in the gene editing technology CRISPR, which allows them to tailor therapies to specific resistance mutations. 1,2 The most promising application of the findings is the potential to resensitize resistant bacteria to standard antibiotics, but the researchers will have Figure 1. CRISPR's double-edged knife.…”
Section: By Stephen Parmley Senior Writermentioning
confidence: 99%